2014
DOI: 10.7860/jcdr/2014/8644.4933
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Aberrations and Polymorphic Evaluation in Males with Primary Infertility from Indian Population

Abstract: Background and objectives: The chromosomal abnormalities are one of the important causes of male infertility. In view of the genetic risks for the next generation, the importance of careful evaluation of karyotype is essential. The objective of this study was to determine the frequency of chromosomal abnormalities in infertile men with primary infertility from Indian population. Materials and Methods:The 78 infertile men with primary infertility, out of which 26 men were azoospermic, 19 men were oligospermic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
1
15
1
Order By: Relevance
“…Studies have reported variable frequency of major chromosomal alterations in patients with male infertility. In our present study, chromosomal alterations in the NOA men were 14.3%, which was higher than published data of the average level (8.2%) and the Indian average level (10.8%) (Akbari, Behjati, Pourmand, Asbagh, & Kachoui, ; Rao et al., ), and were lower than that in some Western countries (14.5%–26.3%) (Akbari et al., ; Akin, Onay, Turker, & Ozkinay, ; Frouzandeh, Saeideh, & Sanaz, ; Kate, Pokale, Jadhav, & Gangane, ; Mohammed et al., ; Rao et al., ). Such variability among different series is likely to be related to a dissimilar composition of the studied populations, mostly to the severity of male factor (Pylyp, Spinenko, Verhoglyad, & Zukin, ).…”
Section: Discussioncontrasting
confidence: 81%
“…Studies have reported variable frequency of major chromosomal alterations in patients with male infertility. In our present study, chromosomal alterations in the NOA men were 14.3%, which was higher than published data of the average level (8.2%) and the Indian average level (10.8%) (Akbari, Behjati, Pourmand, Asbagh, & Kachoui, ; Rao et al., ), and were lower than that in some Western countries (14.5%–26.3%) (Akbari et al., ; Akin, Onay, Turker, & Ozkinay, ; Frouzandeh, Saeideh, & Sanaz, ; Kate, Pokale, Jadhav, & Gangane, ; Mohammed et al., ; Rao et al., ). Such variability among different series is likely to be related to a dissimilar composition of the studied populations, mostly to the severity of male factor (Pylyp, Spinenko, Verhoglyad, & Zukin, ).…”
Section: Discussioncontrasting
confidence: 81%
“…Various numerical and structural chromosome abnormalities were identified in 19.48% of infertile Tunisian men with poor semen quality (Ghorbel et al, 2012) and chromosome analysis revealed major chromosome abnormalities in 10.2% of infertile men in the Indian population (Kate et al, 2014). Karyotype abnormalities were identified in 7.2% of infertile males in Turkey (Cavkaytar et al, 2012) and the total prevalence of chromosomal abnormalities was found to be 4.3% (5/115) in Isparta (South of Turkey) (Kosar et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of chromosomal abnormality in infertile men is 2.1-19.48% (Yatsenko et al, 2010;Fu et al, 2012;Ghorbel et al, 2012;Quan et al, 2013;Ananthapur et al, 2014;Kate et al, 2014). Chromosomal defects may decrease male fertility and increase the history of female adverse fertility outcomes, e.g., recurrent spontaneous abortion or stillbirth.…”
Section: Introductionmentioning
confidence: 99%
“…45,X/46,XY mosaicism were only found in one azoospermic patient. There was no available history of mentioned patient (Kate, Pokale, Jadhav, & Gangane, ).…”
Section: Discussionmentioning
confidence: 99%